2020
DOI: 10.1101/2020.09.24.20100933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-Term Pediatric Acclimatization to Adaptive Hearing Aid Technology

Abstract: Purpose: This pilot study assessed the perceptual, cognitive and academic learning effects of an adaptive integrated directionality and noise reduction hearing aid program in pediatric users. Methods: Fifteen pediatric hearing aid users (6 to 12 years old) participated in a hearing aid pilot with pre- to post-comparisons. Participants received new bilateral, individually fitted Oticon OPN hearing aids programmed with OpenSound Navigator (OSN) processing. Word recognition in noise, sentence repetition in quie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 102 publications
1
2
0
Order By: Relevance
“…It is possible that the difference between these studies was due to the reduced variance associated with retesting the same participants in two test conditions. Previously, we found that word repetition in noise did not improve after 2-3 months of using OSN in a new fitting, but caregiver reports of ability improved over the study period (Pinkl et al, 2021). Here, we report improved word repetition in noise after 7-13 months of continuous use of OSN and Omni.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…It is possible that the difference between these studies was due to the reduced variance associated with retesting the same participants in two test conditions. Previously, we found that word repetition in noise did not improve after 2-3 months of using OSN in a new fitting, but caregiver reports of ability improved over the study period (Pinkl et al, 2021). Here, we report improved word repetition in noise after 7-13 months of continuous use of OSN and Omni.…”
Section: Discussionsupporting
confidence: 41%
“…The system updates 500 times/second across 16 independent frequency channels, enabling a rapid, spatial-based adaptive system with high selectivity to speech sounds (Le Goff et al, 2016). In a previous, exploratory study (Pinkl et al, 2021), we showed that 6-12 year old children fitted with OSN-enabled hearing aids for two months received enhanced caregiver assessments of their speech and sound perception, spatial sound awareness and ability to participate in conversations. However, their measured speech perception, language, cognitive and academic skills were unaffected by using the hearing aids.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation